1998
DOI: 10.1002/(sici)1097-4628(19980228)67:9<1545::aid-app6>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

A GC-MS study of the addition reaction of aryl amines with acrylic monomers

Abstract: ABSTRACT:Previous studies have shown that the interaction of carboxylic acid groups with the amine functionalities of aryl amines, especially secondary and tertiary aryl amines, can lead to the free-radical polymerization of acrylic monomers such as methyl methacrylate. In this study, the Michael addition reaction of primary and secondary aryl amines with acrylic monomers such as acrylic acid (AA) was investigated. Equivalent amounts of either p-toluidine (PT) or N-phenylglycine (NPG) and AA were combined in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 2 publications
1
31
0
Order By: Relevance
“…2 and 3). Based on the present data and previously reported work [18,19,21], possible routes for the conduct of the spontaneous and photo polymerizations of the HAp-incorporated model self-etch adhesives were proposed in Fig. 7.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…2 and 3). Based on the present data and previously reported work [18,19,21], possible routes for the conduct of the spontaneous and photo polymerizations of the HAp-incorporated model self-etch adhesives were proposed in Fig. 7.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, in order to proceed to the second step, that was, decomposition of the complex to generate the free radicals, involvement of external additives such as HAp was required. This proposed route is distinct from the reported studies [18,19,25] that employed carboxylic acids and NPG (or its analogs). In those systems, the interaction of the carboxylic acids with NPG produced rather unstable complex, probably due to the special chemical structure of NPG that combined both acid and amine groups.…”
Section: Discussionmentioning
confidence: 83%
“…On one hand, as a redox system is utilized to initiate the polymerization, formation of a complex among both DMPT-BPO and DEAEMA-BPO is expected, and aromatic branching units and terminal groups derived from the toluidine free radicals are also expected. On the other hand, it has been shown that tertiary amine can induce deprotonation of carboxylic acid functionalities and this in turn leads to free radical polymerization of acrylic monomers [11,12]. For the bone cements prepared in this work, a certain extent of stereocontrol can be expected because the principles of template polymerization are involved.…”
Section: Nmr Characterizationmentioning
confidence: 87%
“…Poly(propylmethylacrylate ethyleneimine) was prepared via reaction of poly(ethyleneimine) with methyl acrylate (known as 'Michael addition' reaction) [43][44][45]. Prior to the reaction, poly-(ethyleneimine) hydrochloric salt was first neutralized with aqueous NaOH solution.…”
Section: Synthesis Of Poly(propylmethylacrylate Ethyleneimine) Ppmaeimentioning
confidence: 99%